Validation of a steam based post-process pasteurization system for control of Listeria monocytogenes in ready-to-eat roast beef - Gill, V.S.; Thippareddi, H.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Listeria monocytogenes has been implicated in outbreaks of illness involving ready-to-eat (RTE) meat products, prompting researchers to look into intervention technologies to reduce or eliminate this risk. In our study roast beef was inoculated with a 5-strain cocktail of Listeria monocytogenes, vacuum-packaged, and then pasteurized at 205°F for 0, 2, 3 or 4 min in a Stork RMS-Protecon Post-Process Pasteurization System. More bacteria were killed as pasteurization time increased. Initial inoculum level was 5.8 log10 CFU/cm2 of product surface area. Pasteurization for 2 min resulted in 2.5 to 2.7 log10 CFU/cm2 reductions. Similar reductions were seen at 3 min. At 4 min pasteurization, L. monocytogenes decreased in roast beef by approximately 4.5 log10 CFU/cm2; over 99.99% had been killed. The Stork steam based system is effective for reducing the risks of L. monocytogenes in RTE roast beef while providing acceptable quality characteristics.
Keywords: Beef; Roast beef; Post-packaging; Ready-to-eat; Steam-Based pasteurization